The validity and reliability of an established series of Badminton-specific field tests - Hughes, M. G.; Pugliese, L.; Andrew, M. (World Badminton Federation, 2016)
Establishing the reliability and validity of fitness assessments is important if test results are used effectively. Measures of reliability describe how consistent the results are from a procedure. If a fitness test is valid, then it is an appropriate method for the evaluation of that specific fitness component. The present study investigated the reliability and validity of Badminton England`s junior testing programme. Throughout the past 15 years Badminton England has administered twice-yearly fitness assessment on their junior national squad players. This comprehensive set of data comprises results from around 220 juniors, 27 of whom have gone on to become senior internationals, so the programme now represents a valuable resource on the development of badminton fitness and is used to guide training and preparation for English junior players. Tests for power and movement speed are included in the testing programme and the purpose of this study is to report the reliability and validity of these procedures in the assessment on Badminton-specific fitness.